'Great Rides' on New Zealand's new national cycleway: pursuing mobility capital. (3rd April 2018) - Bell, Claudia
Abstract: New Zealand has long claimed itself as 'adventure capital of the world', a place to engage in a wide range of adventurous activities. The backdrop: extensive areas of grand landscape. A new form of access to this landscape has been developed with the extensive new cycle trails. To date 19 dedicated routes in diverse scenic locations constitute Nga Haerenga, the national cycleway system. The 60 million enterprise, co-sponsored by national and local government, is a strategy to encourage both domestic and international tourism. Through riding these trails, cyclists of every level of experience and skill expand their own mobility capital. New Zealand's well-established brand as a place of glorious landscape is the significant motif in this project. These Great Rides are the newest agents in this ongoing promotion exercise. The seduction of pretty landscape and the sheer joy of cycling over-ride concerns about local eco-politics.